Thermophilic anaerobic digestion of cattle manure reduces seed viability for four weed species - Eckford, R. E.; Newman, J. C.; Li, X.; Watson, P. R. (International Journal of Agricultural and Biological Engineering, 2012)
Abstract: Anaerobic digestion of manure and other biowaste has been gaining public attention for producing biogas as a renewable energy. More digestate materials after harvesting biogas available will be used as biofertilizers, soil conditioners and amendments for land application. However, digestate is required to be free of weed seeds. The effect of anaerobic digestion on the survival of weed seeds has not been studied extensively. This study examined four weed seeds, wild oats (Avena fatua L.), wild buckwheat (Polygonum convolvulus L.), wild mustard (Sinapis arvensis (DC.) L.C.Wheeler) and volunteer canola (Brassica napus L.) that were placed in batch cultures with feedlot cattle manure at 55